2020
DOI: 10.4081/jphia.2021.1622
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception, public health interventions, and Covid-19 pandemic control in sub-saharan Africa

Abstract: Coronavirus disease 2019 (COVID 19) has had serious social, economic, and health effects globally. The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2), which was first announced in December 2019 has resulted in more than 24 million infections. There is paucity of knowledge on the role of risk perception in the adoption of public health interventions needed to control the spread of COVID 19 infections within communities. This was a scoping review and documents how risk perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
0
18
1
Order By: Relevance
“…[30] Closer to the West African and Senegalese contexts, Aduh and colleagues (2020) reported that in sub-Saharan Africa moderate to high levels of COVID-19 knowledge and perceived risk. [15] Contrary to prior international research, we did not find an association between knowledge and engaging in prevention behaviors. Rather, perceived COVID-19 risk was a stronger predictor of prevention behaviors, which is also supported by previous international research.…”
Section: Health Beliefscontrasting
confidence: 99%
“…[30] Closer to the West African and Senegalese contexts, Aduh and colleagues (2020) reported that in sub-Saharan Africa moderate to high levels of COVID-19 knowledge and perceived risk. [15] Contrary to prior international research, we did not find an association between knowledge and engaging in prevention behaviors. Rather, perceived COVID-19 risk was a stronger predictor of prevention behaviors, which is also supported by previous international research.…”
Section: Health Beliefscontrasting
confidence: 99%
“…This low perception of risk is also a barrier to the use of self-testing. Nevertheless, what this study has identified is the need to tailor appropriate risk communication and education to enable individuals to understand their risks (32), when resorting to malaria treatment in the absence of either a malaria or a COVID-19 test, or self-managing a COVID-19 infection without having at least warned their relatives and other close contacts.…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 international review by Puspitasari and colleagues reported generally high knowledge and awareness about COVID-19, pro-prevention attitudes and high adherence to COVID-19 prevention behaviours like hand washing and social distancing 36. Closer to the West African and Senegalese contexts, Aduh and colleagues reported moderate to high levels of COVID-19 knowledge and perceived risk in sub-Saharan Africa 18…”
Section: Discussionmentioning
confidence: 99%
“…Questions remain about why COVID-19 infections are reportedly low in Africa, in particular in West Africa where there have been 377 cases per 100 000 persons cumulatively. Although a 2020 analysis by Aduh and colleagues reported on perceptions and behaviours towards COVID-19 across sub-Saharan Africa, we have much to learn from populations in densely populated West Africa, a comparatively more urban sub-Saharan region home to more than 400 million people 18 19…”
Section: Introductionmentioning
confidence: 99%